Gerakan Prolanis Sehat di Klinik Azzahra Kota Palembang - Rizma Adlia Syakurah; Siti Halimatul Munawarah; Danny Kusuma Aerosta; Siti Nuraziza Tuzzuhro (Jurnal Medika: Medika, 2026)
Hypertension and diabetes mellitus remain major challenges in healthcare services. The Chronic Disease Management Program (Prolanis), initiated by BPJS Kesehatan, aims to improve the quality of life of participants living with chronic diseases. This community service activity was conducted to enhance the understanding and awareness of Prolanis participants in controlling disease risk factors through health education integrated with basic health screening. The activity was carried out on February 14, 2026, at Azzahra Clinic in Palembang City and involved 33 participants. The methods used included lectures and interactive discussions, distribution of informational leaflets, and health examinations covering blood pressure, body mass index, total cholesterol, and fasting blood glucose according to clinical indications. The results showed that most participants had cardiometabolic risk factors, with 72.7% categorized as prehypertensive, 54.5% classified as overweight or obese, and 60.6% having borderline high cholesterol levels. Among the 17 participants who underwent fasting blood glucose testing, 47.1% were categorized as prediabetic and 35.3% met the criteria for diabetes. These findings highlight the importance of regular health screening and strengthening health education through the Prolanis program to prevent chronic disease complications at an earlier stage.